Mother phubbing and adolescents’ problematic SNS use: the mediating role of perceived burdensomeness and the moderating role of need to belong - Wang, Pengcheng; Ouyang, Mingkun; Yin, Yulong; Li, Biao (Frontiers in Psychology, 2023)
There is a rapidly growing academic interest on parental phubbing, however, no research has explored the association between mother phubbing and adolescent problematic social networking sites use (PSNSU), the underlying mediating and moderating effects in this relationship are also in need to be uncovered. The present study examined whether mother phubbing would be positively related to adolescent PSNSU, whether perceived burdensomeness would mediate this relationship, and whether need to belong would moderate the associations between mother phubbing and adolescent PSNSU. The hypothesized research model was examined among 3915 Chinese adolescents. The results showed that mother phubbing was positively associated with adolescent PSNSU and perceived burdensomeness mediated this association. Furthermore, need to belong moderated the relationship between perceived burdensomeness and PSNSU, the relationship between mother phubbing and perceived burdensomeness, and the relationship between mother phubbing and PSNSU.